Relationship between physical activity and quality of life in pregnant women - Bahadoran, Parvin (Iran J Nurs Midwifery Res, 2015)
BACKGROUND: Physical activity is one of the important factors in predicting the quality of life, which varies between different cultures and countries. The aim of this study was to determine the relationship between physical activity and the quality of life in pregnant women. MATERIALS AND METHODS: This cross-sectional study was carried on 380 pregnant women who were admitted to Isfahan healthcare centers and Shahid Beheshti Hospital, by using the two-stage sampling method (cluster convenience) in 2013. Demographic/pregnancy characteristics, physical activity (36Q) and prenatal quality of life questionnaires (26Q) were completed by the participants. The statistical analyses were performed with various statistical tests such as Student's t-test, one-way analysis of variance (ANOVA), Pearson correlation coefficient, linear regression, and SPSS statistical software version 16. RESULTS: The findings showed that 91.6% of the subjects were 20–35 years old, 69% had a gestational age of 29–37 weeks, 60% had their first pregnancy, 98% had poor physical activities, and 43% had a good quality of life. There was also a negative correlation between physical activity and social support (P = 0.04, r = −0.11). CONCLUSIONS: As the results show high percentage of poor physical activity and quality of life, and also the relationship between these variables, more attention should be dedicated to this problem. Furthermore, structured programs and educational approaches are also needed for pregnant women.